The semantics of multi-headed wh correlatives in Georgian - Thalluri, Natasha (Proceedings of the Linguistic Society of America, 2025)
Existing accounts of Georgian relative clauses mention two relativization strategies, one involving the complementizer rom, and the other involving the relativizing clitic -c. While Foley (2013); Bhatt & Nash (2023) provide a syntactic account of these structures, their semantics remains unstudied. In this paper I present novel data on preposed relative clauses in Georgian formed via the relativizing clitic -c, and argue for a correlative-like semantics of these structures along the lines Dayal 1996’s analysis of Hindi correlatives. Moreover, contra Bhatt & Nash (2023) I argue it is these multiple wh-romelic relative clauses rather than the multiple headed rom relative clauses that pattern like canonical correlatives in terms of definiteness effects, and their ability to license a pair-list interpretation.